Positive leadership strategies for extraordinary performance - Cameron, Kim (Berrett-Koehler, 2012)
Positive Leadership shows how to reach beyond ordinary success to achieve extraordinary effectiveness, spectacular results, and what Kim Cameron calls "positively deviant performance"-performance far above the norm. Citing a wide range of research in organizational behavior, medical science, and psychology as well as real-world examples, Cameron shows that to achieve exceptional success, leaders must emphasize strengths rather than simply focus on weaknesses; foster virtuous actions such as compassion, gratitude, and forgiveness; encourage contribution goals in addition to achievement goals; and enable meaningfulness in work. In this concise, inspiring, and practical guide, Cameron describes four positive leadership strategies, lays out a proven process for implementing them, and includes a self-assessment instrument. This second edition has been updated throughout with new research findings and new ideas for implementing positive leadership.